Photoacoustic measurements of the thermal diffusivity of solids in the presence of a drum effect - SUSZYŃSKI, Z.; MALIŃSKI, M.; BYCHTO, L. (Archives of Acoustics, 1997)
The photoacoustic measurements of the thermal diffusivity of the thick plates of metals are discussed when the drum effect is not quenched. The dominant machanism responsible for the photoacoustic signal was determined. Depending on the configuration arrangement, the ratio of the thermal signal to the thermoelastic bending one was determined. The thermal diffusivity was obtained from both the frequency dependence of the rear amplitude and rear phase characteristics. The influence of the thermoelastic bending on both rear and front frequency characteristics is discussed. The way of calculation of the thermal diffusivity in the case of the results showing strong thermoelastic bending effect is discussed.